Possible involvement of chemokine C‐C receptor 7−programmed cell death‐1+ follicular helper T‐cell subset in the pathogenesis of autoimmune hepatitis. Issue 1 (28th December 2017) - Kimura, Naruhiro; Yamagiwa, Satoshi; Sugano, Tomoyuki; Setsu, Toru; Tominaga, Kentaro; Kamimura, Hiroteru; Takamura, Masaaki; Terai, Shuji
Abstract: Background and Aim: Recent studies have demonstrated that B cells and follicular helper T (Tfh) cells, which are central regulators of humoral immune response, contribute to the development and progression of autoimmune diseases. Because Tfh cells can be divided into several subsets with distinct functional properties, this study aimed to examine the roles of different subsets of circulating Tfh cells in the immune pathogenesis of autoimmune hepatitis (AIH). Methods: Thirty‐five patients with AIH, 28 patients with primary biliary cholangitis, 22 patients with chronic hepatitis B (CHB), and 44 health controls (HC) were enrolled. The frequencies of different Tfh subsets in the blood and liver were examined by flow cytometry and immunohistochemical staining. The function of circulating Tfh subsets was examined after in vitro stimulation. Results: In newly diagnosed AIH patients, the frequency of circulating chemokine C‐C receptor 7 − programmed cell death‐1 + Tfh subset was significantly increased compared with that in CHB patients and HC, significantly correlated with clinical parameters, including serum IgG, prothrombin time and albumin levels, and significantly decreased after corticosteroid treatment. In the liver of AIH patients, the frequencies of activated Tfh subsets were significantly increased and positively correlated with those in the blood. Moreover, the ability to produce interleukin‐21 and interleukin‐17 from circulating Tfh cells was significantly increased in AIH patients compared with HC. Conclusions: These results significantly extend our understanding of Tfh subsets in AIH and suggest a potential role of dysregulated chemokine C‐C receptor 7 − programmed cell death‐1 + Tfh subset in the pathogenesis and disease progression of AIH.